Correlation between structure and optical properties in (Y,Lu)3Al5O12:Ce3+ solid solutions - Zhang, Mei; Li, Bowen; Yang, Yingshu; Chen, Shuijin; He, Xin; Zhao, Fenghua; Zeng, Qingguang (Journal of physics. D, Applied physics, 2016)
A series of (Y,Lu)3Al5O12:Ce3+ (YLuAG:Ce) solid solutions were synthesized via the solid-state reaction route. The phosphors are all of the cubic garnet crystal structures confirmed by x-ray diffraction (XRD). The internal quantum efficiency and emission intensity of the phosphors can be enhanced by increasing the Lu3+ content in the host lattice, along with a blue shift of the emission peak. In addition, the blue shift of the emission peak correlates very well with the lattice contraction. Intense light-emitting diodes (LEDs) are successfully fabricated based on the YLuAG:Ce phosphors and 450 nm blue Ga(In)N chips. The luminous efficiency of YLuAG:Ce phosphors converted LEDs increases with elevating Lu3+ concentration. The results indicate that Ce3+ doped YLuAG solid solutions, especially LuAG:Ce phosphor is a promising green phosphor for solid-state lighting.